A biochemical methane potential of pig slurry - Santos, Andreia D. (2022)
This study assesses the methane production potential for the Anaerobic Digestion of Pig Slurry, using two different Substrate to Inoculum Ratios, 0.65, and 1, and its comparison with the theoretical prediction. The Specific Biogas Production, the Specific Methane Production, and the average methane content were determined for both experiments and adjusted to Standard Temperature (273.15 K) and Pressure (1 atm). The results reached in this study show that the experience conducted with a SIR of 1 produced more volume of biogas, with higher methane content than the one with the lower SIR. With a SIR of 1.0, it was achieved a SMP of 0.568 NL CH4/g VS with an average methane content of 83%. The Technical Digestion Time was found to be 12 days. By comparing the experimental BMP with the estimated value of 0.623 NL CH4/g VS, it was possible to conclude that the estimated value presented a deviation of just 2.96 % during the assay with a SIR of 1.